A concerted SCF-MO ab initio and vibrational spectroscopic study of the conformational isomerism in 2-aminoethanol - Silva, Constança F. P. (1999)
Conformational isomerism in isolated and liquid 2-aminoethanol was investigated by a concerted molecular orbital and vibrational spectroscopic approach. The molecular structures, relative energies, dipole moments and vibrational spectra (both infrared and Raman) of the various possible conformers of the studied compound were calculated, using the extended 6-31G* basis set at the HF-SCF ab initio level of theory. The theoretical results were then used to interpret infrared and Raman data obtained under different experimental conditions. It was found that none of the most populated conformational states existing in the pure liquid (where intermolecular H-bonding occurs extensively)-the gGt and tTt conformers - , correspond to the conformational ground state for the isolated 2-aminoethanol molecule - the intramolecularly H-bonded g'Gg' conformer.